Discovery of putative inhibitors against main drivers of SARS-CoV-2 infection: Insight from quantum mechanical evaluation and molecular modeling - Balogun, Toheeb A.; Chukwudozie, Onyeka S.; Ogbodo, Uchechukwu C.; Junaid, Idris O.; Sunday, Olugbodi A.; Ige, Oluwasegun M.; Aborode, Abdullahi T.; Akintayo, Abiola D.; Oluwarotimi, Emmanuel A.; Oluwafemi, Isaac O.; Saibu, Oluwatosin A.; Chuckwuemaka, Prosper; et al. (Frontiers in Chemistry, 2022)
SARS-CoV-2 triggers a worldwide medical crisis, affecting the world's social, emotional, physical, and economic equilibrium. However, treatment choices and targets for finding a solution to COVID-19's threat are becoming limiting. A viable approach to combating the threat of COVID-19 is to create pharmacological and therapeutic targets by uncovering promising inhibitors and proteins in the viral life cycle of COVID-19. Therefore, in this study, we employ high-throughput virtual screening to screen library of phytocompounds from selected medicinal plants targeting SARS-CoV-2 spike glycoprotein, 3CLpro, PLpro and RdRp. Virtual screening approach have been reported as a promising method to identify biologically active compounds from large libraries. In addition, molecular docking, Prime MM/GBSA (molecular mechanics/generalized born surface area) analysis, molecular dynamics (MD) simulation and pharmacokinetic/drug-likeness model was performed to identify potential phytodrugs. In support to these approaches, we employ series of chemical quantum calculation, semi empirical Hamiltonian and density functional theory analysis to develop therapeutic agents against COVID-19. The results show that structural modification of flavonoids including glycosylation and prenylation significantly contribute to its binding affinity and molecular interactions. The sugar moiety component of flavonoids increases its solubility resulting in reduced toxicity and higher bioavailability. Through protein-ligand mapping and interaction profiling, three lead flavonoids (lonchocarpol A, diplacol and broussonol E) out of the screened compounds library formed essential interactions such as hydrogen bonds and hydrophobic interactions with amino acid residues at the binding pocket of 3CLpro. These molecular interactions coupled with structural binding poses were firmly supported by 100 ns molecular dynamics simulation and chemical quantum analysis, which demonstrated a stable protein-ligand complexes in the active site of SARS-CoV-2 3CLpro. Furthermore, the compounds were observed to be chemically reactive with promising molecular electron potential properties. Pharmacokinetics profiling shows the compounds are druggable molecules with good biosafety profile. Collectively, we propose that the discovered flavonoids may open the way for the establishment of phytodrugs for the management of COVID-19 pandemics and new chemical libraries for preventing COVID-19 entry into the host, based on the findings of this multi-targeted computational investigation.